Systematic analysis of noncanonical ribosomal protein paralogs does not provide evidence for specialized functions in Drosophila - Katarina Z. A. Grobicki; Daniel Gebert; Carol Sun; Felipe Karam Teixeira (Proceedings of the National Academy of Sciences, 2025)
Ribosomes catalyze all protein synthesis, and mutations altering their levels and function underlie many developmental diseases and cancer. Historically considered to be invariant machines, ribosomes differ in composition between tissues and developmental stages, incorporating a diversity of ribosomal proteins (RPs) encoded by duplicated paralogous genes. Here, we use Drosophila to systematically investigate the origins and functions of noncanonical RP paralogs. We show that new paralogs mainly originated through retroposition and that only a few new copies retain coding capacity over time. Although transcriptionally active noncanonical RP paralogs often present tissue-specific expression, we show that the majority of those are not required for either viability or fertility in Drosophila melanogaster . The only exception, RpS5b, which is required for oogenesis, is functionally interchangeable with its canonical paralog, indicating that the RpS5b −/− phenotype results from insufficient ribosomes rather than the absence of an RpS5b-specific, functionally specialized ribosome. Altogether, our results provide evidence that instead of new functions, RP gene duplications provide a means to regulate ribosome levels during development.